Tenko - Riddington, Ken; Roberts, Pennant (London : BBC TV, 1997)
Originally broadcast in 1981, Tenko is the moving story of a group of women thrown together by the choas of World War Two in the horrifying condition of a Japanese prison camp
part 1, 2. Shattered dreams - part 3, 4. Freedom's end - part 5, 6. Sticking together - part 7, 8. Victims of circumstance - part 9, 10. Last days
Part 1-4 in one container
Copy available in DVD format
Writer, Paul Wheeler, Jill Hyem, Anne Valery ; series creator, Lavinia Warner ; composer, James Harpham
Ann Bell, Stephanie Cole, Stephanie Beacham, Patricia Lawrence
Keywords: World War, 1939 - 1945 -- Prisoners and prisons, Japanese; World War, 1939 - 1945 -- Concentration camps -- Japan